A MATLAB tool to study harmonics penetration in grid unbalanced conditions - Zambroni de Souza, M. F.; Pereira, M. L.; Silveira, P. M.; Ribeiro, P. (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
Harmonics is a very important subject in the area of power quality, due to the negative impacts they bring to the network. This paper presents a computational tool using MATLAB to study harmonic penetration in electric grids. The platform is then applied to a distribution system under balanced and unbalanced conditions at different harmonic frequencies. In the first two cases the grid is connected to an infinite bus, so the behavior of a balanced and an unbalanced grid is analyzed. The other two cases consider the grid isolated, once again, balanced and unbalanced conditions are focused. The proposed method employs a direct approach by injecting current of different harmonic levels. The analyses are made by observing the impacts the harmonics brings to the voltages of positive and negative sequence.